Creative Product Development Strategy: Case Study of Acaraki, Kota Tua - Vivaldy Ismail; Rizki Nurul Nugraha; Adinda Yuliani (Westscience Press, 2024)
This article discusses creative product development strategies in the Acaraki food and beverage industry, Kota Tua, Jakarta. The research method used is qualitative, with a descriptive qualitative approach and SWOT analysis. The data collection techniques used are direct observation, interviews, and literature studies. The formulation of the problem; what are the creative products offered by Acaraki Kota Tua, what is the current development strategy of Acaraki Kota Tua, and why is a development strategy needed for Acaraki Kota Tua. The research objectives are to find out the creative products offered by Acaraki Kota Tua to consumers, analyze the current development strategy of Acaraki Kota Tua, and provide insight into the importance of development strategies for the creative industry, especially in the field of food and beverages. The research findings show that Acaraki has succeeded in presenting innovation in promoting Indonesia's cultural heritage through its main product, namely herbal drinks. Not only herbal drink products, but Acaraki also sells food products and also produces herbal drinks in packaged form. There are several obstacles faced by Acaraki, such as the lack of attracting the attention of the younger generation, inadequate marketing, and limited products packaged for tourists as souvenirs. To overcome these problems, Acaraki can implement appropriate strategies, such as expanding branches, entering international markets, increasing promotions, collaborating with the government, and optimizing the use of information technology.